2021
DOI: 10.1002/cite.202000163
|View full text |Cite
|
Sign up to set email alerts
|

Hydroisomerization of Renewable and Fossil n‐Alkanes over Bifunctional Dealuminated ZSM‐5 Catalysts

Abstract: The hydroisomerization of two long-chain n-alkane mixtures was investigated over bifunctional Pt/H-ZSM-5 catalysts before and after dealumination of preshaped zeolite/binder pellets. The hydroisomerization over the dealuminated catalysts leads to more isomers and less cracking products. Consequently, higher ratios of multi-to mono-branched isomerization products are formed as expected for large-rather than medium-pore zeolites. This indicates a higher availability of space in the vicinity of the active sites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…It is found that the isomerization of long-chain n -alkanes is not satisfactory over either large pore (12-member ring pore) molecular sieves (such as SAPO-5) or small pore (8-member ring pore) molecular sieves (such as SAPO-34). Furthermore, over-cracking is also inevitable over medium pore (10-member ring pore) molecular sieves containing curved channels (such as ZSM-5) or channels with side cages (such as MCM-22). Therefore, medium pore molecular sieves (such as SAPO-11, ZSM-22, and ZSM-23) containing one-dimensional straight channels are considered to be suitable acidic supports for isomerization. Their unique pore structures not only improve the diffusion rate of monomethyl isomers within channels but also effectively reduce the formation of dimethyl and polymethyl isomers, which are prone to secondary β-scission.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the isomerization of long-chain n -alkanes is not satisfactory over either large pore (12-member ring pore) molecular sieves (such as SAPO-5) or small pore (8-member ring pore) molecular sieves (such as SAPO-34). Furthermore, over-cracking is also inevitable over medium pore (10-member ring pore) molecular sieves containing curved channels (such as ZSM-5) or channels with side cages (such as MCM-22). Therefore, medium pore molecular sieves (such as SAPO-11, ZSM-22, and ZSM-23) containing one-dimensional straight channels are considered to be suitable acidic supports for isomerization. Their unique pore structures not only improve the diffusion rate of monomethyl isomers within channels but also effectively reduce the formation of dimethyl and polymethyl isomers, which are prone to secondary β-scission.…”
Section: Introductionmentioning
confidence: 99%
“…ANNs are utilized to predict variables processed in a rapid manner and provide precise prediction under a complex process. ANNs are broadly applied for modeling and controlling multipart of chemical reactors and processes to accurately simulate atmospheric distillation columns, 131,132 various of heat exchangers, 133,134 and catalytic reactors. 135,136 Approximation of the reaction rate obtained without a kinetic model would eliminate the errors obtained from choosing of the kinetic method related to the catalyst deactivation models for kinetic constant integration.…”
Section: Mathematical Modeling Of Chemical Reactorsmentioning
confidence: 99%
“…Hydroisomerization of normal long-chain alkanes is critical to improve the quality of gasoline, diesel, and lubricants. Presently, the widely used hydroisomerization catalysts mostly are metal-supported molecular sieves, and the carriers could be ZSM-5, , SAPO-31, , SAPO-5, , , and SAPO-11. Among all of these molecular sieves, SAPO-11 has exhibited its priority in catalytic hydroisomerization reaction due to its mild acidity and suitable pore structure. However, owing to the limitation of the microporous structure of conventional SAPO-11, the diffusion rate of isomerized branched products as well as of the intermediates is retarded resulting in a low selectivity of hydroisomerization. Additionally, its structure of narrow pores easily causes carbon deposition, shortening the life of the bifunctional catalysts.…”
Section: Introductionmentioning
confidence: 99%